The data economy: Implications from Singapore - KUMAR, Sree (Institutional Knowledge at Singapore Management University, 2018)
This book outlines the findings and conclusions of a multidisciplinary team of data scientists, lawyers, and economists tasked with studying both the possibilities of exploiting the rich data sets made available from many human-technology interactions and the practical and legal limitations of trying to do so. It revolves around a core case study of Singapore's public transport system, using data from both the private company operating the contactless payment system (EZ-Link) and the government agency responsible for public transport infrastructure (Land Transport Authority). In analysing both the possibilities and the limitations of these data sets, the authors propose policy recommendations in terms of both the users of large data sets and the legislation necessary to enable these uses while protecting the privacy of users.